SOME PECULIARITIES OF “SOCIAL POWER” AS A SEGMENT IN THE STRUCTURE OF THE POWER CONCEPT IN THE MODERN ENGLISH LANGUAGE - Tatiana M. Shekhovtseva, Elena A. Kamyshanchenko , Irina O. Eshchenko , Natalya I. Kupina , Victoria V. Platoshina (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Studying the mechanisms of verbalization and structuring of concepts remains one of the pressing problems of modern cognitive linguistics. The structure of the POWER concept is outlined by the authors as a multicomponent formation with a complicated structure including the core (image component and encyclopedic field) and the periphery (interpretation field). The aim of the article is to identify and analyze the conceptual features included in the segment "Social Power" belonging to the encyclopedic field of the concept POWER. The methods of definition analysis, contextual analysis, cognitive interpretation. The practical part of the work is based on the analysis of the following conceptual features of the segment “Social power”: 1. Emotional and psychological influence, personal authority; 2. Powers, rights; 3. The power of words. The research shows that the phenomenon of social power has a great importance nowadays and is widely represented in the English language picture of the world.